2014
DOI: 10.1002/dvdy.24178
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal mapping of vascularization and innervation in the fetal murine intestine

Abstract: Background: In mice, the intestinal tube develops from the splanchopleure before embryonic day 9.5. Subsequent patterning of nerves and blood vessels is critical for normal digestive function. A hierarchical branching vascular network allows for efficient nutrient absorption, while the complex enteric nervous system regulates intestinal motility as well as secretion, absorption, and blood flow. Despite the well-recognized significance of these systems, the precise mechanisms by which they develop have not been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(48 citation statements)
references
References 38 publications
1
47
0
Order By: Relevance
“…Nishiyama et al (2012) showed that the major part of the colonic ENS is colonized via transmesenteric routes. In a recent study, it could be demonstrated that primary vascularization is required for NCCs migration, which never enter a region of the gut before the capillary plexus is developed (Hatch and Mukouyama 2014).…”
Section: Figmentioning
confidence: 99%
“…Nishiyama et al (2012) showed that the major part of the colonic ENS is colonized via transmesenteric routes. In a recent study, it could be demonstrated that primary vascularization is required for NCCs migration, which never enter a region of the gut before the capillary plexus is developed (Hatch and Mukouyama 2014).…”
Section: Figmentioning
confidence: 99%
“…During development, the digestive mesenchyme is colonized by vENCCs, endothelial and lymphatic cells [147][148][149][150]. Unexpectedly, the number of vENCCs contributes to the maintenance of stomach identity and differentiation through inhibition of the Notch signaling pathway [72].…”
Section: Discussionmentioning
confidence: 99%
“…This demonstrates that by regulating mesenchyme identity, vENCCs act as a new mediator of mesenchymal-epithelial interactions in the control of gastric epithelial regionalization. The close association of endothelial and lymphatic cells with ENCCs during the establishment of their respective networks and also in adults [148][149][150] opens the way for investigating new potential actors in the regulation of mesenchymal-epithelial interactions during development, but also in adults. Besides smooth muscle, enteric and endothelial cells, the GI wall contains many other cell types (for instance, fibroblasts, lymphocytes and leukocytes) [124] that could be involved in mesenchymal-epithelial interaction mechanisms to maintain the regionalization and homeostasis of digestive epithelia in adults.…”
Section: Discussionmentioning
confidence: 99%
“…In the embryo, developing endodermal and mesodermal organs also become innervated, and these peripheral nerves are required for function of the adult organ (Aven and Ai, 2013;Hatch and Mukouyama, 2015;Pichel et al, 1996). For example, the intestine contains 500 million neurons, and these all derive from neural crest cells that migrate into the gut mesenchyme shortly after gut tube formation.…”
Section: Interactions Between Multiple Germ Layers Improve In Vitro Cmentioning
confidence: 99%